ANALISIS MINAT STAFF KEUANGAN MELAKUKAN FRAUD: PENDEKATAN THEORY OF PLANNED BEHAVIOR DAN FRAUD TRIANGLE THEORY - Muhammad Nadhim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at explaining and predicting factors of individual intention that influence a person to commit fraud. The word individual in this context refers to finance staff. This study uses Theory of Planned Behavior and Fraud Triangle Theory. Using a survey sample, the respondents of this study are 91 people working in the Department of Finance at faculty level and university level. Using PLS (Partial Least Square) as its data analyzing tool, this study finds that Attitude toward Behavior, Perceived Pressure, and Opportunity have a positive impact on the intention of finance staff to commit fraud. However, Subjective Norm and Perceived Behavioral Control do not have significant impact on the intention of finance staff to commit fraud. The implication of this research is that, in order to reduce fraudulent behavior at faculty and university level, the officials of faculty and university should pay attention more to factors that that affect the intention of finance staff to commit fraud; ie. Attitude toward Behavior, Perceived Pressure, and Opportunity.Keywordsi: theory of planned behavior, fraud triangle theory, attitude toward behavior, subjective norm, perceived behavioral control, perceived pressure, opportunity.